2020
DOI: 10.1186/s12979-020-00178-w
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated immunosenescence in rheumatoid arthritis: impact on clinical progression

Abstract: Patients with rheumatoid arthritis (RA) develop features of accelerated ageing, including immunosenescence. These changes include decreased thymic functionality, expansion of late-differentiated effector T cells, increased telomeric attrition, and excessive production of cytokines (senescence-associated secretory phenotype). The progression of RA has been associated with the early development of age-related co-morbidities, including osteoporosis, cardiovascular complications, and cognitive impairment. Here I r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 143 publications
(180 reference statements)
1
56
0
1
Order By: Relevance
“…This indicates that the involvement of the thumb is more relevant at a younger age, possibly rather by destructive than inflammatory processes resulting from an overuse of the thumb. On the other hand, the positive correlation between the rising age and the involvement of the fingers II-V indicates that the prevalence for systemic inflammatory processes, such as in arthritis, is rising with the age [31]. The here presented results show that patients with involvement of the thumb have a worse therapeutic outcome.…”
Section: Discussionmentioning
confidence: 49%
“…This indicates that the involvement of the thumb is more relevant at a younger age, possibly rather by destructive than inflammatory processes resulting from an overuse of the thumb. On the other hand, the positive correlation between the rising age and the involvement of the fingers II-V indicates that the prevalence for systemic inflammatory processes, such as in arthritis, is rising with the age [31]. The here presented results show that patients with involvement of the thumb have a worse therapeutic outcome.…”
Section: Discussionmentioning
confidence: 49%
“…Overall, these data demonstrated a global cognitive decline in RA patients, which was associated with disease activity and immune differences, thus suggesting that peripheral immune imbalance, along with a proinflammatory milieu, could predict the cognitive deficits in RA. Of note, although the presence of higher BDNF plasma levels could seem unusual in patients with chronic inflammation, such as those with RA, it should be considered that the circulating BDNF might largely be derived from leukocytes in inflammatory diseases [ 90 ]. Interestingly, it has been shown that BDNF is constitutively expressed by peripheral blood mononuclear cells (PBMCs) and synovial cells [ 90 ].…”
Section: Biological Factorsmentioning
confidence: 99%
“…Of note, although the presence of higher BDNF plasma levels could seem unusual in patients with chronic inflammation, such as those with RA, it should be considered that the circulating BDNF might largely be derived from leukocytes in inflammatory diseases [ 90 ]. Interestingly, it has been shown that BDNF is constitutively expressed by peripheral blood mononuclear cells (PBMCs) and synovial cells [ 90 ]. Instead, GDNF, whose decreased plasma levels were found to be associated with cognitive dysfunctions in RA patients, is produced only in the central nervous system [ 90 ].…”
Section: Biological Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several features of premature immunosenescence have been observed in RA. These alterations include decreased thymic functionality, expansion of late-differentiated effector T cells, increased telomeric attrition, and increased production of pro-inflammatory cytokines (senescence-associated secretory phenotype) [ 27 ]. A significant expansion of late-differentiated T cells (CD4 + CD28 − and CD8 + CD28 − ) in RA was reported several years ago [ 28 , 29 ], as similarly observed during healthy aging [ 30 ].…”
Section: Introductionmentioning
confidence: 99%